Age at start of using tobacco on the risk of head and neck cancer: pooled analysis in the International Head and Neck Cancer Epidemiology Consortium (INHANCE) - Chang, Chun-Pin; Chuang, Shu-Chun; Berthiller, Julien; Wünsch, Victor; Levi, Fabio; Dal Maso, Luigino; Smith, Elaine; Ramroth, Heribert; Boccia, Stefania; Brenner, Hermann; Boffetta, Paolo (Cancer epidemiology, 2019)
Background - Tobacco use is a well-established risk factor for head and neck cancer (HNC). However, less is known about the potential impact of exposure to tobacco at an early age on HNC risk. - Methods - We analyzed individual-level data on ever tobacco smokers from 27 case-control studies (17,146 HNC cases and 17,449 controls) in the International Head and Neck Cancer Epidemiology (INHANCE) consortium. Adjusted odds ratios (ORs) and 95% confidence intervals (CIs) were estimated using random-effects logistic regression models. - Results - Without adjusting for tobacco packyears, we observed that younger age at starting tobacco use was associated with an increased HNC risk for ever smokers (OR<10 years vs. ≥30 years: 1.64, 95% CI: 1.35, 1.97). However, the observed association between age at starting tobacco use and HNC risk became null after adjusting for tobacco packyears (OR<10 years vs. ≥30 years: 0.97, 95% CI: 0.80, 1.19). In the stratified analyses on HNC subsites by tobacco packyears or years since quitting, no difference in the association between age at start and HNC risk was observed. - Conclusions - Results from this pooled analysis suggest that increased HNC risks observed with earlier age at starting tobacco smoking are largely due to longer duration and higher cumulative tobacco exposures.
Gesehen am 04.05.2020